Behaviour of wintering Tundra Swans Cygnus columbianus columbianus at the Eel River delta and Humboldt Bay, California, USA - Gress, Carol; Byers, Jacob W; Jennings, Emily; Ely, Craig (Wildfowl, 2013)
Tundra Swan Cygnus columbianus columbinanus phenology and behaviour at the Eel River delta and southern Humboldt Bay in northern California, USA, is described. Counts made each January from 1963 onwards peaked at 1,502 swans in 1988. Monthly counts recorded during the 2006/07 and 2008/09 winters peaked in February, at 1,033 and 772 swans respectively. Swans roosted on ephemeral ponds at the Humboldt Bay National Wildlife Refuge, on ephemeral ponds within grassland pastures in the vicinity of the Refuge, and perhaps also used the Eel River as a roost. Flights between Refuge roosts and the pastures and ponds occurred in the two hours after sunrise and before dark. In winters 2008/09 and 2009/10, the percentage of cygnets in the flocks was 10.6% and 21.4% respectively, and increased to =31% cygnets each year after most swans had departed from the area in March. Average brood size in 2009/10 was 2.1 cygnets. Daily activities consisted of foraging (44.9% of activities recorded), comfort behaviour (22.1%), locomotion (16.2%) and vigilance (15.5%). Eight neck-collared swans identified in the wintering flock were marked at four locations in different parts of Alaska, up to 1,300 km apart.